2017
DOI: 10.1002/ca.22923
|View full text |Cite
|
Sign up to set email alerts
|

Aortic arch origin of the left vertebral artery

Abstract: Complications from anterior approaches to the cervical spine are uncommon with normal anatomy. However, variant anatomy might predispose one to an increased incidence of injury during such procedures. We hypothesized that left vertebral arteries that arise from the aortic arch instead of the subclavian artery might take a more medial path in their ascent making them more susceptible to iatrogenic injury. Fifty human adult cadavers were examined for left vertebral arteries having an aortic arch origin and these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Therefore, a better understanding of their anatomy as seen in the present study is important for spine surgeons who often depend on anatomical landmarks for avoiding vulnerable neurovascular structures during surgical approaches. 28-31 Our study revealed that these branches are always present on both sides and the anterior surface of the esophagus should be avoided while retracting it to minimize the risk of postoperative dysphagia.…”
Section: Resultsmentioning
confidence: 79%
“…Therefore, a better understanding of their anatomy as seen in the present study is important for spine surgeons who often depend on anatomical landmarks for avoiding vulnerable neurovascular structures during surgical approaches. 28-31 Our study revealed that these branches are always present on both sides and the anterior surface of the esophagus should be avoided while retracting it to minimize the risk of postoperative dysphagia.…”
Section: Resultsmentioning
confidence: 79%
“…Li et al [ 50 ] confirmed this variant, as the LVA with an anomalous origin entered the TF at C5 and presented a sinuous course. Tardieu et al [ 94 ] also found that AA-originating LVAs were more likely to enter the TF more cranially than C6 and to adopt a more medial course over the cervical vertebral bodies.…”
Section: Discussionmentioning
confidence: 99%
“…However, no direct correlation with anatomical variation and postoperative retropharyngeal hematoma have been identified. 12 - 15 The superior and inferior thyroid arteries have been identified as etiology of hemorrhage in some retrospective reviews of postoperative hematoma after ACDF, although most reported cases do not have an identifiable source of hemorrhage. 16 , 17 …”
Section: Discussionmentioning
confidence: 99%